2009
DOI: 10.1002/ange.200901384
|View full text |Cite
|
Sign up to set email alerts
|

Enantiospezifische Synthese und Allylierung ausschließlich Kohlenstoff‐substituierter, α‐chiraler Allylstannane

Abstract: Endlich frei wurde der Weg zu den Titelverbindungen in nahezu enantiomerenreiner Form mit einem Bis(triorganostannyl)zinkreagens (siehe Schema). Diastereoselektive thermische (links) und Lewis‐Säure‐vermittelte Folgereaktionen (rechts) veranschaulichen das Synthesepotenzial dieser Verbindungen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…[33,34] Initial screening showed that it was indeed possible to generate allylic stannanes 19-21 in near quantitative yields but their isolation and determination of their enantiomeric excesses by GLC or HPLC failed. [36] We therefore processed fragile 19-21 directly in thermal allylation reactions with benzaldehyde. [58] The corresponding homoallylic alcohols 22-24 were obtained in moderate yields, typical for this transformation.…”
Section: Allylic Substitutionmentioning
confidence: 99%
See 2 more Smart Citations
“…[33,34] Initial screening showed that it was indeed possible to generate allylic stannanes 19-21 in near quantitative yields but their isolation and determination of their enantiomeric excesses by GLC or HPLC failed. [36] We therefore processed fragile 19-21 directly in thermal allylation reactions with benzaldehyde. [58] The corresponding homoallylic alcohols 22-24 were obtained in moderate yields, typical for this transformation.…”
Section: Allylic Substitutionmentioning
confidence: 99%
“…With the chemistry of (R 3 Si) 2 Zn unexplored, we set out to examine the generation of (R 3 Si) 2 Zn32–34 and that of the related (R 3 Sn) 2 Zn35, 36 (Scheme ). For this, corresponding R 3 SiCl and R 3 SnCl are treated with lithium to form R 3 SiLi and R 3 SnLi,31 respectively.…”
Section: Conjugate Additionmentioning
confidence: 99%
See 1 more Smart Citation